THE DECLINE OF INDIAN AGRICULTURE AND TRADITIONAL INDUSTRIES DURING THE COLONIAL PERIOD: A HISTORICAL ANALYSIS - Kumari, Preeti (International Journal of Research -GRANTHAALAYAH, 2025)
This research paper critically analyzes the process and causes of the decline of two main pillars of the Indian economy – agriculture and traditional handicrafts – under British colonial rule. The primary focus of the research is to examine how the economic policies of the East India Company and later the British Crown transformed India's centuries-old self-sufficient rural economy into a 'colonial dependent economy'. In the context of agriculture, this paper highlights the adverse effects of new land revenue systems (such as the Permanent Settlement and the Ryotwari system) and the forced commercialization of agriculture, which pushed farmers into debt and famine. On the other hand, in the realm of traditional industries, this research examines the process of 'deindustrialization,' where competition from British machine-made goods and discriminatory tariff policies destroyed the Indian textile and metal industries. The study's findings suggest that this decline of agriculture and industries was not merely an economic transformation but a systematic process of 'drain of wealth' that created structural distortions in the Indian socio-economic fabric. Based on primary and secondary historical sources, this research argues that colonial policies laid the foundation for modern Indian economic backwardness.